Moderating Role of Credibility and Ad Liking Between Online Advertisement and Consumer Buying Behavior of University Students of Pakistan - Khalid, Rizwan; Tehreemyasmeen, Tehreemyasmeen (UI Scholars Hub, 2021)
Research aim: The motivation behind the study is to see the effect of online ad on shopper conduct just from the university understudy point of view. Methodology: There are five autonomous factors in the study and one is the reliant variable. The study information is gathered from 300 respondents and put into the SPSS to make the determination through Multiple Regression. Theoretical contribution: The study is beneficial for the theory developers and the readers who are interested in designing the advertisement for youth because university students mostly consist of youth who have different thought of opinion because they are open to vast environment which is impacting on their thoughts. Research implication: The study demonstrates that 56.4 for each penny variety in ward variable is because of autonomy and reasoned that online promotion significantly affects shopper purchasing conduct and it is a huge section.